Research Collaboration and Thematic Evolution in Green Accounting Disclosure and Sustainability Reporting: A Bibliometric Analysis - Fujianti, Lailah (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to map the research collaboration structure and thematic evolution of Green Accounting Disclosure (GAD) and Sustainability Reporting (SR) based on publications indexed in the Dimensions database during the 2021–2026 period. A bibliometric approach was employed using data retrieved from the Dimensions database through searches with the keywords “Green Accounting Disclosure” and “Sustainability Reporting.” The analysis was conducted using VOSviewer software and incorporated several bibliometric techniques, including co-occurrence analysis, co-authorship analysis, organizational network analysis, country collaboration analysis, overlay visualization, and density visualization. The findings reveal a substantial increase in publications related to GAD and SR throughout the observation period, with research productivity reaching its peak in 2025. Keyword analysis identified several dominant research themes, including information, board, state, crisis management, and technique, highlighting the growing importance of information transparency, corporate governance, and sustainability management within this research domain. Temporal visualization further demonstrates a thematic shift from an initial emphasis on environmental management and regulatory compliance toward more advanced approaches centered on sustainability measurement, Environmental, Social, and Governance (ESG) indicators, and data-driven evaluation frameworks. Collaboration network analysis indicates that the United States contributed the largest number of publications, while the University of Ghana emerged as the most influential institution within the research network. The results suggest that the development of GAD and SR research has been driven by the combined effects of increasing global scientific collaboration and the transformation of research themes toward more integrated, measurable, and sustainability-oriented perspectives. This study provides a comprehensive overview of the intellectual landscape of GAD and SR research and identifies promising directions for future scholarly investigations.